Analisis Karakteristik Lingkungan Pada Kejadian Leptospirosis di Kabupaten Demak Jawa Tengah Tahun 2009 - Ikawati, Bina; Sulistiyani, Sulistiyani; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2009)
ABSTRACT Background: Leptospirosis is a zoonosis disease caused by Leptospira bacteria and transmitted to human by contact with contaminated animal urin or contaminated environment. Leptospirosis cases in Demak district increased for 4 year later. Until April 15th 2008, there were 62 leptospirosis cases with CFR=9,67%. The aim of this research was to determine environmental characteristic related to leptospirosis incidence in Demak district. Method: It was an observational research using a case control design with 44 cases and 44 controls. Cases were leptospirosis diagnosed by leptotek dri dot in Demak Health District Agency. Controls were neighbour of leptospirosis cases who didn’t have clinically symptom of leptospirosis, with age and sex appropiate to inclusion criteria. Laboratory diagnosis with leptotek dri dot had done for controls who agreed to sign inform consent. Data were analyzed using chi square test at α=5%. Variable with p value<0,25 would be continued with multivariat test using Regressi Logistic - Backward Likehood Ratio method. Result: The result of this research showed that there were 10 controls with no clinical diagnosis but positive at leptotek dri dot diagnosis. At statistical analysis 10 cases and 10 controls dropped. Univariat analysis showed controls and cases have environmental risk factor and knowledge, attitude, practice about leptospirosis similarly. Bivariat analysis showed there was no relationship between environmental characteristic and knowledge, attitude, practice with leptospirosis. Test of water sample had been done at 8 location. One of them of creek showed positif contain Leptospira sp. Rat trapped had been done at four location, showed trap succes about 8,7%-29,8%. Eventhough environment factor and knowledge, attitude, practice showed there were no but water from ditch that positif Leptospira sp, significant association and highly succes at rat trapped were concidered to be the risk of leptospirosis transmission. Keywords : environment, leptospirosis, Demak